A Quality Improvement Project Aimed at Reducing Patient Falls in Ambulatory Clinics - Patricia Macolino; Katie Fox; Rebecca Fitzpatrick; Vivek N. Ahya; Ilona Lorincz; Barbara Prior (Patient Safety)
# Introduction